High-dispersion alkyne hydrogenation catalyst, preparation method and application thereof

CN120001366BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311516488.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2026-10-13
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

但Ni的还原温度往往要达到450℃左右,在该温度下还原态的Pd金属极易聚集,使催化剂活性大幅度下降,需要大幅度增加活性组分等量以补偿活性损失,但又会引起选择性的下降

Benefits of technology

[0046]本发明提供一种高分散度的负载型催化剂,通过引入助剂,加入调控物改变载体表面等电点及采取相应的表面处理方法,可大幅提高氧化铝载体表面羟基基团密度。在后续制备的贵金属催化剂中,贵金属活性组分可在载体表面形成高分散、粒径小的活性中心。并且通过配方、制备方法的组合及工艺参数的改变,可精细调控催化剂表面活性组分密度,进而适配不同类型的多相催化体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004549783010000111
    Figure BDA0004549783010000111
  • Figure BDA0004549783010000131
    Figure BDA0004549783010000131
Patent Text Reader

Abstract

The application provides a high-dispersion acetylene hydrogenation catalyst and a preparation method and application thereof. By introducing an additive, adding an isoelectric point regulator in the preparation process of alumina, and combining corresponding alkalization, acidification, irradiation, and crystallization surface treatment methods to change the surface properties and inhibit the sintering phenomenon of the active component at high temperatures, the dispersion of the Pd metal on the surface of the catalyst can be greatly improved, and the catalytic performance and selectivity are obviously improved. In the carbon four acetylene hydrogenation reaction, the content of acetylene in the product can be greatly reduced, and the loss of butadiene is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalysts, specifically relating to a highly dispersed alkyne hydrogenation catalyst, its preparation method, and its application. Background Technology

[0002] Currently, the main source of C4 hydrocarbons in China is the byproducts of ethylene cracking units. The C4 components in the cracked gas contain a large amount of alkynes such as methylacetylene, ethylacetylene, and vinylacetylene. Hydrogenation to increase their saturation yields 1,3-butadiene, an important industrial feedstock, thereby improving the overall efficiency of the steam cracking unit, increasing the utilization rate and added value of ethylene unit byproducts, and generating considerable economic benefits. The hydrogenation process must not only eliminate alkynes as much as possible but also minimize the loss of 1,3-butadiene, which places high demands on the catalytic performance and selectivity of the catalyst. Furthermore, to ensure long-term operation of the unit and reduce production costs, the catalyst should possess high stability.

[0003] Studies have shown that noble metal catalysts exhibit high selectivity for alkyne hydrogenation. Chinese patent CN113663688A discloses a method for preparing an alkyne-containing C4 hydrogenation catalyst with a bimodal pore distribution structure. The method involves sequentially impregnating a support in A: a Pd salt solution; B: a microemulsion containing Ni and Cu precursor salts, an oil phase, a surfactant, and a co-surfactant; C: a Mo salt solution; and D: a microemulsion containing Pd precursor salts, an oil phase, a surfactant, and a co-surfactant, followed by drying and calcination to obtain the target catalyst. This catalyst can be used in alkyne-containing C4 hydrogenation processes, exhibiting good hydrogenation activity and high resistance to coking.

[0004] Chinese patent CN101428228A discloses a method for preparing a selective hydrogenation catalyst. The method involves preparing a solution containing 0.1–0.5% palladium, impregnating it onto an alumina support containing alkali metals, alkaline earth metals, or mixtures thereof, followed by drying and calcination to obtain a catalyst precursor. The catalyst precursor is then subjected to stepwise or co-impregnation with a soluble salt solution containing copper, element IVA, and auxiliary metals, followed by drying and calcination to obtain the catalyst. This catalyst is suitable for the selective hydrogenation of alkyne-rich residues after butadiene extraction, but it is only suitable for processing C4 materials with high alkyne content and very low butadiene content.

[0005] Patent CN104096572A discloses a hydrogenation catalyst in which the active components are Pd, Ag, and Ni. Pd and Ag are supported using an aqueous solution impregnation method, while Ni is supported using a W / O microemulsion impregnation method. Using this method, Pd / Ag and Ni are located in pores of different sizes, allowing the generated green oil to undergo saturated hydrogenation in the macropores, thus reducing catalyst coking. However, the reduction temperature of Ni often reaches around 450℃, at which temperature reduced Pd metal easily aggregates, causing a significant decrease in catalyst activity. This necessitates a substantial increase in the amount of active components to compensate for the activity loss, but this in turn leads to a decrease in selectivity.

[0006] The aforementioned inventions attempt to improve the catalytic performance and selectivity of catalysts from multiple perspectives, but they have limited utilization efficiency of the active components and cannot provide a more effective solution to the spontaneous aggregation of noble metals contained in the active components on the surface during the reduction process. Furthermore, the preparation process is lengthy and complex, involves the addition of numerous additives, resulting in high production costs, and generally requires the use of surfactants, organic ligands, and other organic compounds, which are not environmentally friendly. Therefore, there is still a need to develop catalysts with simple preparation methods, good performance, and stability. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a highly dispersed alkyne hydrogenation catalyst and its preparation method. This invention achieves a significant increase in the density of hydroxyl groups on the alumina support surface by adding an appropriate amount of isoelectric point modifier during the alumina support preparation process, thereby influencing the distribution of noble metal active components on the surface and improving the dispersion of the noble metals.

[0008] One of the objectives of this invention is to provide a highly dispersed alkyne hydrogenation catalyst, comprising a modified alumina support and active components and additives supported on the support, wherein the dispersion of the active components on the catalyst surface is 40-70%.

[0009] According to the present invention, in the highly dispersed alkyne hydrogenation catalyst:

[0010] The dispersion of the active component on the catalyst surface is 45-65%;

[0011] The content of the auxiliary agent is 0.01-10% based on the total weight of the catalyst (100%), preferably 0.05-8%.

[0012] The catalyst has an average pore size of 30–200 nm, preferably 50–150 nm; a most probable pore size of 80–250 nm, preferably 100–200 nm; and a specific surface area of ​​5–100 m². 2 / g, preferably 10-70m 2 / g; the bulk density is 0.4 to 1.3 g / mL, preferably 0.5 to 1.2 g / mL.

[0013] According to the present invention, in the highly dispersed alkyne hydrogenation catalyst:

[0014] The active component is Pd;

[0015] The adjuvant is selected from at least one of Ag and Ce;

[0016] The modified alumina carrier comprises alumina and other oxides, wherein the other oxides are selected from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, zirconium oxide, manganese oxide, cerium oxide, iron oxide, ferrous oxide, titanium oxide, copper oxide, zinc oxide, lanthanum oxide, nickel oxide, magnesium oxide, yttrium oxide, gallium oxide, and indium oxide, preferably from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, titanium oxide, zirconium oxide, nickel oxide, magnesium oxide, gallium oxide, and copper oxide.

[0017] The second objective of this invention is to provide a method for preparing the above-mentioned highly dispersed alkyne hydrogenation catalyst, comprising: immersing the modified alumina support in a metal compound solution containing an active component precursor compound and an auxiliary precursor compound, removing it, drying it, and calcining it to obtain the highly dispersed alkyne hydrogenation catalyst.

[0018] According to the present invention, in the method for preparing the highly dispersed alkyne hydrogenation catalyst:

[0019] The active component precursor compound is selected from palladium nitrate, palladium chloride, palladium oxide, palladium hydroxide, and sodium tetrachloropalladate, preferably from at least one of palladium nitrate and palladium chloride;

[0020] The auxiliary agent precursor compound is selected from at least one of silver nitrate, cerium nitrate, and cerium chloride, preferably from at least one of silver nitrate and cerium nitrate;

[0021] In the metal compound solution, the molar concentration of the active component precursor compound is 0.05–10 mol / L;

[0022] In the metal compound solution, the molar concentration of the auxiliary precursor compound is 0.05–10 mol / L;

[0023] The drying conditions are: a drying temperature of 60–200°C and a drying time of 5–20 h; preferably, a drying temperature of 80–150°C and a drying time of 6–16 h.

[0024] The calcination conditions are as follows: calcination temperature is 200-1200℃, and calcination time is 2-24h; preferably, the calcination temperature is 300-1000℃, and the calcination time is 5-12h.

[0025] According to the present invention, the modified alumina carrier is prepared by the following steps: mixing components including alumina precursor, forming agent, pore expander, isoelectric point regulator, and crosslinking agent solution to obtain a mixture, kneading and shaping, extruding and pelletizing, drying, and calcining to obtain a modified alumina precursor, and then performing surface treatment on the modified alumina precursor to obtain the modified alumina carrier.

[0026] According to the present invention, in the preparation of the modified alumina support:

[0027] The alumina precursor is selected from at least one of boehmite powder, pseudoboehmite powder, trihydrate alumina powder, fast-degrading alumina powder, and θ-alumina powder.

[0028] The molding agent is selected from at least one of starch, methylcellulose, carboxymethylcellulose, ethylcellulose, and hydroxypropyl methylcellulose;

[0029] The pore-expanding agent is selected from at least one of guar gum powder, starch, polyethylene glycol, polyethylene microspheres, polyethylene oxide, polystyrene, and polypropylene glycol;

[0030] The isoelectric point modifier is selected from at least one of oxides with an isoelectric point less than 6 or greater than 8. Preferably, the oxide with an isoelectric point less than 6 is selected from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, zirconium oxide, manganese oxide, cerium oxide, iron oxide, ferrous oxide, and titanium oxide, and more preferably from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, titanium oxide, and zirconium oxide; and / or, the oxide with an isoelectric point greater than 8 is selected from at least one of copper oxide, zinc oxide, lanthanum oxide, nickel oxide, magnesium oxide, yttrium oxide, gallium oxide, and indium oxide, and more preferably from at least one of nickel oxide, magnesium oxide, gallium oxide, and copper oxide.

[0031] The crosslinking agent in the crosslinking agent solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, acetic acid, citric acid, oxalic acid, ascorbic acid, and salicylic acid;

[0032] The solvent in the crosslinking agent solution is selected from at least one of water, methanol, ethanol, and ethylene glycol, preferably from water and / or ethanol.

[0033] According to the present invention, in the preparation of the modified alumina support:

[0034] Based on the total weight of the alumina precursor, forming agent, pore expander, and isoelectric point regulator being 100%, the amount of the forming agent is 0.1-15%, the amount of the pore expander is 0.05-15%, and the amount of the isoelectric point regulator is 0.02-12%; preferably, based on the total weight of the alumina precursor, forming agent, pore expander, and isoelectric point regulator being 100%, the amount of the forming agent is 1-12%, the amount of the pore expander is 1-10%, and the amount of the isoelectric point regulator is 0.1-8%.

[0035] The molar concentration of the crosslinking agent solution is 0.001–10 mol / L, preferably 0.05–5 mol / L; and / or,

[0036] Based on the amount of the alumina precursor being 100g, the amount of the crosslinking agent solution being 50-1000mL, preferably 100-800mL.

[0037] According to the present invention, in the preparation of the modified alumina support:

[0038] The drying conditions are: a drying temperature of 60–200°C and a drying time of 5–20 h; preferably, a drying temperature of 80–150°C and a drying time of 6–16 h.

[0039] The calcination conditions are as follows: calcination temperature is 500–1500℃, and calcination time is 1–24h; preferably, the calcination temperature is 800–1300℃, and the calcination time is 3–15h.

[0040] The surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point less than 6 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 lower than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 1.5 lower; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8, and alkalization is used instead of acidification, the pH of the alkalization treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 1.5 higher.

[0041] The acidification conditions are as follows: temperature 30–100℃, time 0.5–12 h, acidifying agent selected from at least one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, sodium bisulfate, acetic acid, oxalic acid, and citric acid, and the concentration of the acidifying agent solution is 0.01–10 mol / L; preferably, the acidification conditions are as follows: temperature 35–80℃, time 1–8 h, acidifying agent selected from at least one of sulfuric acid, hydrochloric acid, nitric acid, acetic acid, and citric acid, and the concentration of the acidifying agent solution is 0.1–5 mol / L;

[0042] The alkalization conditions are as follows: temperature 30–100℃, time 0.5–12 h, alkalizing agent selected from at least one of sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, and ammonia water, and the concentration of the alkalizing agent solution is 0.01–10 mol / L; preferably, the alkalization conditions are as follows: temperature 35–80℃, time 1–8 h, alkalizing agent selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate, and the concentration of the alkalizing agent solution is 0.1–5 mol / L;

[0043] The crystallization conditions are: a temperature of 50–300°C and a time of 0.5–20 h, and the crystallization solvent is selected from at least one of water, methanol, ethanol, ethylene glycol, and ethylenediamine; preferably, the crystallization conditions are: a temperature of 100–200°C and a time of 1–15 h, and the crystallization solvent is selected from at least one of water, methanol, and ethanol.

[0044] The irradiation conditions are as follows: the radiation source is gamma rays, the irradiation dose rate is 0.01–50 kGy / min, and the irradiation time is 0.1–10 h; preferably, the irradiation conditions are as follows: the radiation source is gamma rays, the irradiation dose rate is 0.5–20 kGy / min, and the irradiation time is 0.2–6 h.

[0045] The third objective of this invention is to provide the application of the above-mentioned highly dispersed alkyne hydrogenation catalyst or the highly dispersed alkyne hydrogenation catalyst obtained by the above preparation method in the selective hydrogenation reaction of C4.

[0046] This invention provides a highly dispersed supported catalyst. By introducing promoters, adding modifiers to change the isoelectric point of the support surface, and employing appropriate surface treatment methods, the density of hydroxyl groups on the alumina support surface can be significantly increased. In the subsequently prepared noble metal catalyst, the noble metal active component can form highly dispersed, small-particle-size active centers on the support surface. Furthermore, by combining formulations and preparation methods, and changing process parameters, the density of active components on the catalyst surface can be precisely controlled, thereby adapting it to different types of heterogeneous catalytic systems. Detailed Implementation

[0047] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0048] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0049] Example 1

[0050] Prepare 250 mL of 0.5 mol / L nitric acid aqueous solution, add it to a mixture of 200 g boehmite powder, 10 g ethyl cellulose, 8 g guar gum powder and 6 g silicon dioxide (isoelectric point 2.2), knead in a kneader to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry at 120 °C for 6 h, calcine at 1160 °C for 6 h, then crystallize the particles in 200 mL of methanol at 150 °C for 12 h, and finally acidify with 200 mL of citric acid solution at 40 °C and pH 1.5 for 7 h, and dry at 120 °C for 6 h to obtain the carrier.

[0051] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 450 °C for 8 h to obtain the target catalyst A1.

[0052] Example 2

[0053] Prepare 250 mL of 0.25 mol / L sulfuric acid aqueous solution, add it to a mixture of 200 g boehmite powder, 12 g methyl cellulose, 6 g guar gum powder and 6 g nickel oxide (isoelectric point 10.5), knead in a kneader to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry at 120 °C for 6 h, calcine at 1200 °C for 6 h, then crystallize the particles in 150 mL of 2 mol / L ethanol aqueous solution at 180 °C for 8 h, and finally alkalize with 200 mL of sodium hydroxide aqueous solution at 45 °C and pH 11.5 for 8 h, and dry at 120 °C for 6 h to obtain the carrier.

[0054] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 400 °C for 8 h to obtain the target catalyst A2.

[0055] Example 3

[0056] Prepare 250 mL of an aqueous solution of 0.2 mol / L sulfuric acid and 0.2 mol / L citric acid, add it to a mixture of 120 g θ-alumina powder, 80 g fast-degrading alumina powder, 10 g ethyl cellulose, 8 g starch, and 8 g vanadium pentoxide (isoelectric point 1.3), knead in a kneader to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry at 120 °C for 6 h, calcine at 1120 °C for 6 h, then acidify the particles with a 200 mL sulfuric acid solution at 70 °C and pH 0.5 for 5 h, and finally irradiate the particles with γ rays at a dose rate of 3 kGy / min for 4 h, and dry at 120 °C for 6 h to obtain the carrier.

[0057] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 480 °C for 8 h to obtain the target catalyst A3.

[0058] Example 4

[0059] Prepare 250 mL of an aqueous solution of 0.2 mol / L hydrochloric acid, 0.2 mol / L acetic acid, and 0.1 mol / L citric acid. Add this solution to a mixture of 100 g boehmite powder, 100 g alumina trihydrate powder, 10 g ethyl cellulose, 8 g starch, and 8 g copper oxide (isoelectric point 9.5). Knead the mixture in a kneader to form a plastic semi-solid material. Then, extrude the mixture into spherical particles with a diameter of 3 mm. Dry the particles at 120 °C for 6 h, calcine them at 1060 °C for 6 h, and then irradiate them with γ-rays at a dose rate of 2 kGy / min for 5 h. Finally, alkalize the particles with 200 mL of potassium hydroxide at 50 °C and pH 10.5 for 6 h, and dry them at 120 °C for 6 h to obtain the carrier.

[0060] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 420 °C for 8 h to obtain the target catalyst A4.

[0061] Example 5

[0062] Prepare an aqueous solution of 0.2 mol / L nitric acid, 0.15 mol / L sulfuric acid, and 0.2 mol / L citric acid in 250 mL. Add this solution to a mixture of 100 g boehmite powder, 100 g rapid alumina powder, 10 g hydroxymethyl cellulose, 10 g polypropylene glycol, and 8 g antimony pentoxide (isoelectric point 2). Knead the mixture in a kneader to form a plastic semi-solid material. Then, extrude the mixture into spherical particles with a diameter of 3 mm. Dry the particles at 120 °C for 6 h, calcine them at 1150 °C for 6 h, crystallize them in 150 mL of 2 mol / L ethanol aqueous solution at 120 °C for 12 h, irradiate them with γ-rays at a dose rate of 5 kGy / min for 2 h, and finally acidify them with 200 mL of sulfuric acid at 60 °C and pH 1.1 for 5 h, and dry them at 120 °C for 6 h to obtain the carrier.

[0063] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 400 °C for 8 h to obtain the target catalyst A5.

[0064] Example 6

[0065] Prepare 250 mL of an aqueous solution of 0.15 mol / L nitric acid, 0.15 mol / L acetic acid, and 0.1 mol / L citric acid. Add this solution to a mixture of 200 g boehmite powder, 12 g carboxymethyl cellulose, 8 g starch, 6 g polyacrylamide, and 6 g vanadium pentoxide (isoelectric point 1.3). Knead the mixture in a kneader to form a plastic semi-solid material. Then, extrude the mixture into spherical particles with a diameter of 3 mm. Dry the particles at 120 °C for 6 h, calcine them at 1190 °C for 6 h, crystallize them in 200 mL of methanol at 120 °C for 15 h, and then acidify them in 200 mL of sulfuric acid solution at 50 °C and pH 0.4 for 6 h. Finally, irradiate the particles with γ-rays at a dose rate of 2 kGy / min for 5 h and dry them at 120 °C for 6 h to obtain the carrier.

[0066] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 850 °C for 8 h to obtain the target catalyst A6.

[0067] Comparative Example 1

[0068] Prepare 250 mL of 0.25 mol / L sulfuric acid aqueous solution, add it to a mixture of 200 g of fast-degrading alumina powder, 10 g of hydroxymethyl cellulose, and 8 g of polyethylene microspheres, put it into a kneader and knead it to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry it at 120 °C for 6 h, and calcine it at 1160 °C for 6 h to obtain the carrier.

[0069] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 450 °C for 8 h to obtain the target catalyst B1.

[0070] Comparative Example 2

[0071] Prepare 250 mL of 0.5 mol / L nitric acid aqueous solution, add it to a mixture of 200 g boehmite powder, 10 g ethyl cellulose, and 8 g guar gum powder, knead in a kneader to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, then crystallize the particles in 200 mL of methanol at 150 °C for 12 h, and finally acidify with 200 mL of 0.1 mol / L citric acid solution at 40 °C for 7 h, and dry at 120 °C for 6 h to obtain the carrier.

[0072] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 420 °C for 8 h to obtain the target catalyst B2.

[0073] Comparative Example 3

[0074] Prepare 250 mL of an aqueous solution of 0.3 mol / L hydrochloric acid and 0.2 mol / L acetic acid, add it to a mixture of 200 g boehmite powder, 10 g starch, 8 g polypropylene glycol, and 6 g nickel oxide (isoelectric point 10.5), knead in a kneader to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry at 120 °C for 6 h, calcine at 1090 °C for 6 h, then crystallize the particles in 200 mL of methanol at 150 °C for 12 h, and finally acidify with 200 mL of 0.1 mol / L citric acid solution at 40 °C for 7 h, and dry at 120 °C for 6 h to obtain the carrier.

[0075] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 480 °C for 8 h to obtain the target catalyst B3.

[0076] Comparative Example 4

[0077] Prepare 250 mL of an aqueous solution of 0.15 mol / L nitric acid, 0.15 mol / L acetic acid, and 0.05 mol / L citric acid. Add this solution to a mixture of 100 g boehmite powder, 100 g θ-alumina powder, 10 g starch, 8 g guar gum powder, and 6 g vanadium pentoxide (isoelectric point 1.3). Knead the mixture in a kneader to form a plastic semi-solid material. Then, extrude the mixture into spherical particles with a diameter of 3 mm. Dry the particles at 120 °C for 6 h, calcine them at 1190 °C for 6 h, and then acidify the particles with a 200 mL citric acid solution at 40 °C and pH 0.5 for 7 h. Finally, dry the particles at 120 °C for 6 h to obtain the carrier.

[0078] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 410 °C for 8 h to obtain the target catalyst B4.

[0079] Comparative Example 5

[0080] Prepare 250 mL of 0.25 mol / L sulfuric acid aqueous solution, add it to a mixture of 200 g of fast-degrading alumina powder, 10 g of hydroxymethyl cellulose, and 8 g of polyethylene microspheres, put it into a kneader and knead it to form a plastic semi-solid material, then extrude it into spherical particles with a diameter of 3 mm, dry it at 120 °C for 6 h, and calcine it at 1160 °C for 6 h to obtain the carrier.

[0081] Take the above support and prepare 150 mL of a mixed aqueous solution of palladium nitrate and silver nitrate containing 5 g palladium and 5 g silver. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 850 °C for 8 h to obtain the target catalyst B5.

[0082] Comparative Example 6

[0083] Prepare 250 mL of an aqueous solution of 0.2 mol / L nitric acid, 0.15 mol / L sulfuric acid, and 0.2 mol / L citric acid. Add this solution to a mixture of 200 g boehmite powder, 10 g starch, 8 g polyethylene glycol, and 6 g silicon dioxide (isoelectric point 2.2). Knead the mixture in a kneader to form a plastic semi-solid. Then, extrude the mixture into spherical particles with a diameter of 3 mm. Dry the particles at 120 °C for 6 h, calcine them at 1150 °C for 6 h, and then crystallize them in 200 mL of methanol at 170 °C for 10 h. Finally, acidify the particles with 200 mL of citric acid solution at 40 °C and pH 1.5 for 7 h, and dry them at 120 °C for 6 h to obtain the carrier.

[0084] Take the above support and prepare 150 mL of a palladium nitrate aqueous solution containing 5 g of palladium. Saturate the support with the solution and remove it after 5 min. Dry it at 120 °C for 6 h and calcine it in air at 450 °C for 8 h to obtain the target catalyst B6.

[0085] Test Example 1: Catalyst Property Characterization

[0086] Pd dispersion was tested using a Micromeritics AutoChem 2920 adsorption analyzer, with tests performed before and after reduction treatment. First, the sample was purged with He gas at 400℃ for 1 h, then reduced with H2 at 150℃ for 1 h, and finally injected with CO via pulsed injection at 50℃. The CO signal was recorded using a TCD. The CO to Pd adsorption ratio (molar ratio) was 1:1.2 when calculating the dispersion.

[0087] The specific surface area of ​​the catalysts in the examples and comparative examples was determined by the nitrogen physical adsorption BET method; the bulk density of the catalyst was determined by weighing 50 mL of the support (the arithmetic mean of three test results was recorded); the average pore size and most probable pore size were determined by mercury intrusion porosimetry. The above test results are summarized in Table 1.

[0088] Table 1

[0089]

[0090] As shown in Table 1, the method described in this invention can significantly improve the dispersion of Pd metal on the catalyst surface with almost no impact on specific surface area, bulk density, average pore size, or most probable pore size. At excessively high reduction temperatures, the surface-treated support effectively suppresses the sintering of Pd metal on the catalyst surface, maintaining highly dispersed and small-sized active centers. After prolonged catalytic reaction and regeneration, the surface-treated support effectively maintains the high dispersion of Pd metal on the catalyst surface, ensuring the catalyst retains high catalytic performance. Furthermore, by adjusting the type of raw materials, optimizing the proportion of raw materials, changing the combination and sequence of surface treatment methods, and altering the reduction temperature, the dispersion of Pd metal on the catalyst surface can be controlled, thus adapting to different heterogeneous catalytic systems.

[0091] Evaluation of Catalytic Performance of Catalyst in Test Example 2

[0092] The C4 selective hydrogenation catalytic performance of catalysts A1–A6 and B1–B5 was evaluated. The C4 selective hydrogenation reaction conditions were as follows:

[0093] The molar ratio of acetylene to hydrogen was 1:10, the reaction temperature was 45℃, the reaction pressure was 0.8 MPa, the composition of the mixed C4 gas is shown in Table 2, and the volume hourly space velocity was 40 h⁻¹. -1 The remaining amount of alkynes and the loss of butadiene for each catalyst in the reaction are listed in Table 3.

[0094] Table 2

[0095] Isobutane 1.72 n-Butane 4.04 cis-2-butene 3.24 trans-2-butene 4.42 1-Butene 13.17 Isobutylene 19.16 1,2-Butadiene 0.22 1,3-Butadiene 53.48 Methylacetylene (MA) 0.12 Vinylacetylene (VA) 0.40 Ethylacetylene (EA) 0.13

[0096] Both raw materials and products were analyzed by gas chromatography. The total alkyne residue was the sum of the residues of VA, EA, and MA in the product. The butadiene loss was calculated as follows: L = ω f -ω p Where L is the butadiene loss; ω f The butadiene content in the raw material; ω p This refers to the butadiene content in the product.

[0097] After the initial evaluation, catalysts A1–A6 and B1–B5 were regenerated under the following conditions: a steam to air volume ratio of 1:2, a reaction temperature of 500℃, a reaction pressure of 0.1 MPa, and a volume hourly space velocity of 5000 h⁻¹. -1 After regeneration, the C4 selective hydrogenation catalytic performance of catalysts A1-A6 and B1-B6 at 110℃ was evaluated again under the same conditions as above. The amount of alkyne residue and butadiene loss of each catalyst in the reaction are listed in Table 3.

[0098] Table 3

[0099]

[0100] As can be seen from the results in Table 3, the catalysts prepared by the method provided by this invention exhibit superior activity and selectivity compared to catalysts prepared by existing methods. In particular, catalysts A1, A2, A5, and A6, prepared under optimized conditions, demonstrate even better catalytic performance.

[0101] By comparing Example 1 with Example 3, and Example 1 with Example 2, it can be seen that both acidification and alkalization processes can improve the performance of the catalyst.

[0102] The comparison between Example 1 and Comparative Example 6 shows that the introduction of the additive can improve the dispersion of the active component, thereby improving the catalyst performance.

[0103] The comparison between Example 1 and Comparative Example 5 shows that the catalyst prepared by multiple surface treatment methods has better catalytic performance than the catalyst prepared by a single surface treatment method.

[0104] A comparison between Example 1 and Comparative Example 3 shows that when the acidification / alkalization conditions used are inconsistent with the conditions required by the isoelectric point regulator, there is no significant improvement in catalyst performance and selectivity.

[0105] The comparison between Comparative Example 2 and Comparative Example 5 shows that the reduction should be carried out in a suitable temperature range. Excessively high reduction temperatures will lead to a decrease in the catalytic performance and selectivity of the catalyst.

[0106] The comparison between Example 5 and Example 6 and Comparative Example 5 shows that the surface-treated catalyst can effectively suppress the performance degradation caused by high-temperature reduction and maintain a high alkyne conversion rate and selectivity.

[0107] By comparing Example 1 with Comparative Example 1, and Example 6 with Comparative Example 5, it can be seen that the above surface treatment method can enable the catalyst to maintain high catalytic performance after long-term catalytic reaction and regeneration treatment, and can be reused multiple times.

Claims

1. A highly dispersed alkyne hydrogenation catalyst, comprising a modified alumina support and an active component and an additive supported on the support, wherein the active component is Pd and the additive is Ag; the components, including an alumina precursor, a forming agent, a pore-expanding agent, an isoelectric point modifier, and a crosslinking agent solution, are mixed to obtain a mixture, kneaded, extruded, granulated, dried, and calcined to obtain a modified alumina precursor, and then the modified alumina precursor is surface-treated to obtain the modified alumina support; the alumina precursor is selected from boehmite powder and pseudoboehmite. The alumina powder is selected from at least one of stone powder, alumina trihydrate powder, fast-release alumina powder, and θ-alumina powder; the forming agent is selected from at least one of methylcellulose, carboxymethylcellulose, and ethylcellulose; the pore-expanding agent is selected from at least one of guar gum powder, starch, and polypropylene glycol; the isoelectric point regulator is selected from at least one of oxides with an isoelectric point less than 6 or greater than 8; the oxide with an isoelectric point less than 6 is selected from at least one of vanadium pentoxide, antimony pentoxide, and silicon oxide; and the oxide with an isoelectric point greater than 8 is selected from at least one of nickel oxide and copper oxide. The crosslinking agent in the crosslinking agent solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, acetic acid, and citric acid; the solvent in the crosslinking agent solution is selected from water; based on the total weight of the alumina precursor, forming agent, pore expander, and isoelectric point regulator being 100%, the amount of the forming agent is 4.42~5.36%, the amount of the pore expander is 2.68~4.39%, and the amount of the isoelectric point regulator is 2.59~3.54%; the molar concentration of the crosslinking agent solution is 0.25~0.55 mol / L ... The amount of the aluminate precursor used is 100g, and the amount of the crosslinking agent solution used is 125mL; the drying conditions are: drying temperature of 120℃ and drying time of 6h; the calcination conditions are: calcination temperature of 1060~1200℃ and calcination time of 6h; the surface treatment is selected from one of acidification or alkalization, and at least one of crystallization or irradiation. When the isoelectric point regulator is an oxide with an isoelectric point less than 6 and acidification is used, the pH of the acidification treatment needs to be 0.7~0 lower than the isoelectric point value of the isoelectric point regulator.9; When the isoelectric point regulator is an oxide with an isoelectric point greater than 8, and no acidification treatment is used but an alkalization treatment is used, the pH of the alkalization treatment needs to be 1 higher than the isoelectric point value of the isoelectric point regulator; the acidification conditions are: temperature 40~70℃, time 5~7h, and the acidifying agent is selected from at least one of sulfuric acid and citric acid; the alkalization conditions are: temperature 45~50℃, time 6~8h, and the alkalizing agent is selected from at least one of sodium hydroxide and potassium hydroxide; the crystallization conditions are: temperature 120~180℃, time 8~15h, and the crystallization solvent is selected from at least one of methanol, ethanol, and aqueous ethanol solution; the irradiation conditions are: the radiation source is gamma rays, and the irradiation dose rate is 2~5 The irradiation rate was kGy / min, and the irradiation time was 2-5 h. The modified alumina support was impregnated in a metal compound solution containing an active component precursor compound and an auxiliary agent precursor compound. After removal, it was dried and calcined to obtain the highly dispersed alkyne hydrogenation catalyst. The active component precursor compound was palladium nitrate, and the auxiliary agent precursor compound was silver nitrate. In the metal compound solution, the concentration of the active component precursor compound was 5 g / 150 mL, and the concentration of the auxiliary agent precursor compound was 5 g / 150 mL. The drying conditions were: drying at 120℃ for 6 h; the calcination conditions were: calcination temperature of 400-850℃, and calcination time of 8 h.

2. The catalyst according to claim 1, characterized in that, Based on the total weight of the catalyst (100%), the content of the auxiliary agent is 0.01~10%; and / or, The catalyst has an average pore size of 30-200 nm; and / or, a most probable pore size of 80-250 nm; and / or, a specific surface area of ​​5-100 m². 2 / g; and / or, with a bulk density of 0.4~1.3g / mL.

3. The catalyst according to claim 2, characterized in that, Based on the total weight of the catalyst (100%), the content of the auxiliary agent is 0.05-8%; and / or, The catalyst has an average pore size of 50-150 nm; and / or, a most probable pore size of 100-200 nm; and / or, a specific surface area of ​​10-70 m². 2 / g; and / or, with a bulk density of 0.5~1.2g / mL.

4. The catalyst according to any one of claims 1 to 3, characterized in that, The modified alumina carrier comprises alumina and other oxides, wherein the other oxides are selected from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, zirconium oxide, manganese oxide, cerium oxide, iron oxide, ferrous oxide, titanium oxide, copper oxide, zinc oxide, lanthanum oxide, nickel oxide, magnesium oxide, yttrium oxide, gallium oxide, and indium oxide.

5. The catalyst according to claim 4, characterized in that, The other oxides are selected from at least one of vanadium pentoxide, antimony pentoxide, silicon oxide, tin oxide, titanium oxide, zirconium oxide, nickel oxide, magnesium oxide, gallium oxide, and copper oxide.

6. A method for preparing the highly dispersed alkyne hydrogenation catalyst according to any one of claims 1 to 5, comprising: The modified alumina support is immersed in a metal compound solution containing active component precursor compounds and auxiliary precursor compounds, then removed, dried, and calcined to obtain the highly dispersed alkyne hydrogenation catalyst.

7. The application of a highly dispersed alkyne hydrogenation catalyst according to any one of claims 1 to 5, or a highly dispersed alkyne hydrogenation catalyst obtained by the preparation method according to claim 6, in a C4 selective hydrogenation reaction.

Citation Information

Patent Citations

  • Selective hydrogenation catalyst and method of producing the same

    CN101428228A

  • Selective hydrogenation catalyst for improving coking resistance

    CN104096572A

  • Preparation method of alkyne-containing C4 hydrogenation catalyst

    CN113663688A

  • Method for preparing a selective hydrogenation catalyst

    CN109562369A